Analisis pemanasan oven untuk destilasi uap-air dengan hasil panas matahari pada biji buah pala di Kabupaten Fakfak - Rusdin, R.; Mustari, M.; Iswar, M. (Universitas Mataram, 2023)
Nutmeg seeds drying in Fakfak Regency still apply the traditional method, namely, placing the seeds on tarpaulins or mats under the sun. The problem is that the sun’s temperature depends on the weather. Therefore, the oven-drying method should be applied. Steam-water distillation is steam-water heat from a tube (pan) which is heated using firewood. Oven drying can be controlled in terms of temperature and duration to increase production effectiveness and efficiency. Based on the results of the oven and sunlight heating, the following moisture contents were obtained. Heating for 2 hours resulted in an average of 16.71% STDV1.99; 4-hour heating brought about an average of 16.10% STDV 1.53; 6-hour heating produced an average of 13.87% STDV 0.56; 8-hours heating turned out0 an average of 10.17% STDV 0.05; and an average of 8.57% STDV 0.42 for normal heating. According to SNI 01-0006-1993, from the moisture-contents testing for 3 quality categories, the moisture content of 10.54% was for quality 1 (ABCD), 8.64% for quality 2 (RIMPEL) and 11.92% for quality 3 (BWP). Accordingly, the SNI quality requirements for the maximum moisture content of nutmeg seeds was 10%; quality 1 and quality 2 met SNI requirements. The research revealed that, according to SNI, the 9-day solar heating resulted in a quality of category 2 meanwhile the 9-day oven-heating on the nutmeg seeds produced a quality of category 1